Appropriate NH4+/NO3– Ratio Triggers Plant Growth and Nutrient Uptake of Flowering Chinese Cabbage by Optimizing the pH Value of Nutrient Solution - Zhu, Yunna; Qi, Baifu; Hao, Yanwei; Liu, Houcheng; Sun, Guangwen; Chen, Riyuan; Song, Shiwei (Frontiers in Plant Science, 2021)
Compared with sole nitrogen (N), the nutrition mixture of ammonium (NH4+) and nitrate (NO3–) is known to better improve crop yield and quality. However, the mechanism underlying this improvement remains unclear. In the present study, we analyzed the changes in nutrient solution composition, content of different N forms in plant tissues and exudates, and expression of plasma membrane (PM) H+-ATPase genes (HAs) under different NH4+/NO3– ratios (0/100, 10/90, 25/75, 50/50 as control, T1, T2, and T3) in flowering Chinese cabbage. We observed that compared with the control, T1 and T2 increased the economical yield of flowering Chinese cabbage by 1.26- and 1.54-fold, respectively, whereas T3 significantly reduced plant yield. Compared with the control, T1–T3 significantly reduced the NO3– content and increased the NH4+, amino acid, and soluble protein contents of flowering Chinese cabbage to varying extents. T2 significantly increased the N use efficiency (NUE), whereas T3 significantly decreased it to only being 70.25% of that of the control. Owing to the difference in N absorption and utilization among seedlings, the pH value of the nutrient solution differed under different NH4+/NO3– ratios. At harvest, the pH value of T2 was 5.8; in the control and T1, it was approximately 8.0, and in T3 it was only 3.6. We speculated that appropriate NH4+/NO3– ratios may improve N absorption and assimilation and thus promote the growth of flowering Chinese cabbage, owing to the suitable pH value. On the contrary, addition of excessive NH4+ may induce rhizosphere acidification and ammonia toxicity, causing plant growth inhibition. We further analyzed the transcription of PM H+-ATPase genes (HAs). HA1 and HA7 transcription in roots was significantly down-regulated by the addition of the mixture of NH4+ and NO3–, whereas the transcription of HA2, HA9 in roots and HA7, HA8, and HA10 in leaves was sharply up-regulated by the addition of the mixture; the transcription of HA3 was mainly enhanced by the highest ratio of NH4+/NO3–. Our results provide valuable information about the effects of treatments with different NH4+/NO3– ratios on plant growth and N uptake and utilization.